PENGETAHUAN DAN SIKAP MAHASISWA TENTANG UPAYA PENERAPAN KAWASAN TANPA ROKOK (KTR) DI FAKULTAS TEKNIK UNIVERSITAS DIPONEGORO SEMARANG - Herwinda Kurniasih; Bagoes Widjanarko; Ratih Indraswari (Jurnal Kesehatan Masyarakat (Undip), 2016)
Due to the high number of smokers, Semarang City Government issued several regulations on Smokefree Outdoor Areasin order to improve our public health. Based on the National Economic Social Survey in 2004, the health risks for smokers among others: 9,8% of deaths due to chronic lung disease and emphysema, 5% of stroke, increased risk of impotence in men by 50%. Currently there are more than 43 million children aged 0-14 years of living with smokers experiencing slow lung growth. Also, they are more susceptible to respiratory infections, ear infections, and asthma. Smokefree Outdoor Areas is a room or area where it is strictly prohibited toproduce, sale, advertise, promote and/or use the cigarettes. One of Smokefree Outdoor Areas which the society and environment play an important role in community’s behavior is college. One of the reasons why so many students still smoke is because their college haven’t apply the Smokefree Outdoor Areas regulations yet.Purpose:The purpose of this research is to assess knowledge and attitude students on efforts of the implementation of Smokefree Outdoor Areas in the Faculty of Engineering Diponegoro University. This is descriptive research with quantitative approach method where the population is all students in Faculty of Engineering Diponegoro University. Samples were taken from 99 people with purposive sampling technique.Result :After analyzing data using univariate descriptive analysis method, the obtained result showed the knowledge of students about Smokefree Outdoor Areas regulationswas good enough with the percentage 60,9%. Also, students point of view about Smokefree Outdoor Areas was good enough with the percentage 69,7%. The degree of knowledge affects the behavioral changes because attitude is influenced by cognitive components.Conclusion : Hence, it is suggested that Faculty of Engineering issued a decree regarding the Smokefree Outdoor Areas regulation in the campus of the Faculty of Engineering.